2011
DOI: 10.1681/asn.2011020200
|View full text |Cite
|
Sign up to set email alerts
|

Prorenin Receptor Is Essential for Podocyte Autophagy and Survival

Abstract: The prorenin receptor (PRR) is highly expressed in podocytes, but its role in the maintenance of podocyte function is unknown. Here we generated podocyte-specific PRR-knockout mice and found that these animals died between 2 to 3 wk after birth. Within 14 d, PRR-knockout mice developed nephrotic syndrome, albuminuria with podocyte foot-process fusion, and cytoskeletal changes. Podocyte-specific PRR deletion also led to disturbed processing of multivesicular bodies and enrichment of autophagosomal (LC3) and lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
166
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(184 citation statements)
references
References 35 publications
16
166
2
Order By: Relevance
“…This could also in part explain the decreased insulin secretion in cells with ATP6ap2 knocked down. ATP6ap2 has been shown to be involved in the maintenance of acidity within secretory vesicles (62). Previously, it was demonstrated that whole body knock-out of ATP6ap2 was lethal in mice (63); whereas, tissue specific knock-out studies of ATP6ap2 in cardiomyocytes or in podocytes resulted in detrimental defects after birth including heart failure or renal failure, respectively (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…This could also in part explain the decreased insulin secretion in cells with ATP6ap2 knocked down. ATP6ap2 has been shown to be involved in the maintenance of acidity within secretory vesicles (62). Previously, it was demonstrated that whole body knock-out of ATP6ap2 was lethal in mice (63); whereas, tissue specific knock-out studies of ATP6ap2 in cardiomyocytes or in podocytes resulted in detrimental defects after birth including heart failure or renal failure, respectively (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…24 (Pro)renin receptor-bound renin and prorenin display increased enzymatic activity, and binding activates intracellular signaling, upregulating the expression of profibrotic proteins. 25,26 However, new data now suggest that (pro)renin receptor is functionally linked to the vacuolar proton-ATPase [27][28][29] ; therefore, the role of (pro) renin receptor as a part of the RAS remains controversial. The independent identification of possible intracellular isoforms of renin in rodents and humans provides further support for alternative mechanisms that act to locally generate A-II and to partition the local and systemic effects of the hormone.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, v-ATPase is a multisubunit proton pump involved in diverse and fundamental cellular physiology, and v-ATPasemediated acidification, requiring its accessory unit Atp6ap2, was shown to play a pivotal role in canonical and noncanonical Wnt signaling pathways (14 -16). Furthermore, several studies on conditional knock-out mice specific for the heart and kidney cells revealed that Atp6ap2 is essential for v-ATPase-associated autophagy, leading to the maintenance of cell structure and survival (17)(18)(19). More recently, we have shown that Atp6ap2 interacts with partitioning defective 3 homolog, one of the major cell polarity determinants, and contributes to laminar formation during retinal development in mice (20).…”
mentioning
confidence: 97%